PENGEMBANGAN MEDIA POWERPOINT MOTION GRAPHICS SEDERHANA DALAM MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR - Anisa, Nur; Uswatun, Din Azwar; Sutisnawati, Astri (PD PGMI se Indonesia, 2021)
This study aims to: (1) develop technology-based learning media using PowerPoint in the form of simple motion graphics; (2) Knowing the feasibility of the product developed; (3) Knowing how to increase the ability to understand science concepts for fifth-grade elementary school students using development products; (4) Student response to product development. The data collection instruments used were product feasibility questionnaires, student response questionnaires, and tests. With the analysis of the feasibility questionnaire data using the conversion of the quality score of the development product, and the student response questionnaire using the percentage conversion of the Likert scale questionnaire, and the conversion of qualitative to quantitative data. While the test data analysis technique uses gain-score. The results of the product development feasibility study, obtained a final score of 34.25 (very good) for the content and objectives feasibility component, 34 (good) for the instructional feasibility component, and 57.25 (very good) for the technical feasibility component. The results of the effectiveness of product development on students' ability to understand science concepts obtained a score of 0.66 in the first trial and 0.67 in the second trial with the category of moderate improvement criteria. The results of student responses to product development are very strong with a percentage of 85.72% on the content and objectives component, 84.61% on the instructional component, and 89.23% on the technical component.